2019
DOI: 10.1021/acs.biomac.9b01024
|View full text |Cite
|
Sign up to set email alerts
|

DMSO-free cryopreservation of chondrocytes based on zwitterionic molecule and polymers

Abstract: Cartilage tissue engineering highly relies on the ability to store and transport chondrocytes in order to be clinically successful. Cryopreservation is a most reliable technology for chondrocyte storage, but it suffers from the intrinsic toxicity of current state-of-the-art cryoprotectant, dimethyl sulfoxide (DMSO). In this work, we used the first fully zwitterionic compound-based approach for effective chondrocyte cryopreservation. A zwitterionic molecule combined with zwitterionic polymers could balance intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…However, continually increasing the betaine concentration in the cryo-medium did not improve the post thaw cell survival rate. There may exist a maximum of intracellular betaine absorbed by UCMSCs, which is likely related to the transmembrane transport manner of betaine and the expression of transporter on UCMSCs [ 32 ]. According to the result, this maximum of intracellular betaine could only provide limited protection during UCMSCs cryopreservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, continually increasing the betaine concentration in the cryo-medium did not improve the post thaw cell survival rate. There may exist a maximum of intracellular betaine absorbed by UCMSCs, which is likely related to the transmembrane transport manner of betaine and the expression of transporter on UCMSCs [ 32 ]. According to the result, this maximum of intracellular betaine could only provide limited protection during UCMSCs cryopreservation.…”
Section: Discussionmentioning
confidence: 99%
“…This potentials supported its selection as a novel cell cryopreservation CPA. However, for specific cell types like chondrocytes, stem cells, and dendritic cells, betaine alone cannot work well because of insufficient intracellular cryoprotections [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the combination of betaine and PSBMA could provide intracellular and extracellular cryopreservation. 60 Miermont et al observed that increasing osmotic compression decreases protein mobility, resulting in the cessation of several cellular processes. The rate of decrease in cellular processes was exponential when the osmotic compression was on the verge of stalling.…”
Section: Mechanisms Of Cryoprotection Using Macromolecular Cryoprotectantsmentioning
confidence: 99%
“…Chondrocytes were able to attach to substrates with a regular morphology, as opposed to cells cryopreserved in DMSO, which floated as the normal chondrocyte population was also significantly altered. 60 Besides this, Yang et al reported the use of natural biocompatible osmoprotectants in protecting cells from osmotic injury and serve as an ideal CPA. The biocompatible osmoprotectants -proline, glycine, and taurine -were assessed for their cytotoxicity.…”
Section: Mechanisms Of Cryoprotection Using Macromolecular Cryoprotectantsmentioning
confidence: 99%
See 1 more Smart Citation